Motivation, Migration and Non-standard Employment: A Survey Among Temporary Agency Workers - Underthun, Anders; Aasland, Aadne (Nordic Journal of Working Life Studies, 2018)
Research suggests that migrants have a greater tendency to end up in nonstandard employment arrangements than native citizens do, but less attention has been paid to motivational differences within and between migrant groups. On the basis of a survey of temporary agency workers in Norway, we investigate the effect of different country backgrounds on the perceived suitability of nonstandard employment (NSE) at present and in the future. For the perceived current suitability, we find less variation between country backgrounds, but Norwegian workers are much less likely to accept NSE as suitable in the future. An ordinal regression shows that motivation (positive and negative) rather than country background is the strongest predictor of finding NSE employment suitable. As such, the article contributes to understandings about voluntary or involuntary motivations to engage in NSE in a way that informs discussions about migrants in different power positions in a Nordic labor market context.